Rhabdomyosarcoma in a congenital pigmented nevus - Schmitt, F. C. [UNESP]; Bittencourt, A.; Mendonca, N.; Dorea, M. (Taylor & Francis, 1992)
A 7-month-old boy had a giant pigmented lesion involving the trunk and thighs that exhibited many hyperpigmented hairy and verrucous nevi. One of the nevi ulcerated and on histological examination consisted of pleomorphic rhabdomyosarcoma cells that stained for muscle-specific actin (HHF-35), desmin, and myoglobin. Around the tumor, in the dermis, benign pigmented nevus cells were observed. The occurrence of malignant tumors, other than malignant melanoma, in pigmented nevi is rarely described.
Keywords: case report; histology; human; human tissue; immunohistochemistry; infant; male; melanocytic nevus; rhabdomyosarcoma; Actins; Case Report; Desmin; Human; Immunohistochemistry; Infant; Keratin; Male; Nevus, Pigmented; Rhabdomyosarcoma; Skin; Skin Neoplasms; Vimentin